New aspects of spillover effect in catalysis for development of highly active catalysts - International Conference on New Aspects of Spillover effect in Catalysis for Development of Highly Active Catalysts (3rd : 1993 : Kyoto, Japan); Tetsuro, Inui (Amsterdam : Elsevier, 1993)
42